U.S. Antarctic policy : Hearing.94th Congress, 1st Session on U.S. policy with respect to mineral exploration and exploitation in the Antarctic - United States. Congress. Senate. Committee on Foreign Relations. Subcommittee on Oceans and International Environment. (Washington : USGPO, 1975)
Executive hearing held May 15, 1975; made public July 6, 1975 Bibliographical references Mode of access: Internet.